2013
DOI: 10.1515/mammalia-2012-0096
|View full text |Cite
|
Sign up to set email alerts
|

Trophic interactions between puma and endemic culpeo fox after livestock removal in the high mountains of central Argentina

Abstract: This study presents the first data on the diet of the puma ( Puma concolor ) and an endemic culpeo fox ( Pseudalopex culpaeus smithersi ) in the high mountains of central Argentina, based on scat analysis. Trophic interactions of both carnivores were examined from 2003 to 2008 inside a protected area after livestock removal. A total of 604 scats were analyzed. Native species (small cavids and cricetine rodents) were most frequently consumed (58 % -100 % ) by both carnivores. Exotic prey were consumed more in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 42 publications
(77 reference statements)
2
21
1
2
Order By: Relevance
“…Lagomorphs were the next largest diet component, making up 12% relative frequency of concurrency, but most of those were rabbits as opposed to hares. In contrast to our observations, studies of culpeo fox diet in other areas reveal that lagomorphs are often an important prey item [30,47,50], indicating that culpeo foxes may be exhibiting a diet shift away from hares, when pumas are present and guanacos are scarce. The high proportion of fruits and seeds present in the diet of culpeo foxes could also play a role in trophic niche segregation, as it has been previously reported for other opportunistic generalist predators that are more carbohydrate tolerant, like the pine marten (Martes martes) [107], and the red fox [108].…”
Section: Trophic Dietary Overlapcontrasting
confidence: 99%
See 1 more Smart Citation
“…Lagomorphs were the next largest diet component, making up 12% relative frequency of concurrency, but most of those were rabbits as opposed to hares. In contrast to our observations, studies of culpeo fox diet in other areas reveal that lagomorphs are often an important prey item [30,47,50], indicating that culpeo foxes may be exhibiting a diet shift away from hares, when pumas are present and guanacos are scarce. The high proportion of fruits and seeds present in the diet of culpeo foxes could also play a role in trophic niche segregation, as it has been previously reported for other opportunistic generalist predators that are more carbohydrate tolerant, like the pine marten (Martes martes) [107], and the red fox [108].…”
Section: Trophic Dietary Overlapcontrasting
confidence: 99%
“…where: B is the modified Gladfelter-Johnson's index; FO i is the frequency of occurrence of the i prey species; σ is the standard deviation of occurrence frequencies; and R is the number of prey-species consumed by the carnivore guild. We also calculated the Pianka's dietary niche overlap index [90] as a measure of trophic niche overlap between pumas and culpeo foxes Equation 7, given its frequent use in diet studies (e.g., [30,31,91,92]):…”
Section: Scat Collection and Diet Analysismentioning
confidence: 99%
“…Nevertheless, different studies conducted on the guanaco population reintroduced in QCNP indicated that the individuals that survive the critical post-release stage were adapted in terms of behaviour [ 25 ], habitat selection [ 26 ], and diet [ 27 ]. Preliminary evidence shows that the guanacos could contribute to the ecological restoration of the area (unpublished data), reinforcing the importance of this project focused on restoring natural processes rather than addressing only extinction risk [ 53 ].…”
Section: Discussionmentioning
confidence: 96%
“…However, these studies have been conducted at the interspecific level and the conclusions may not hold true at the intraspecific level where species‐specific ecological and life history characteristics may have a strong influence on the processes that drive population phenotypic variation. For instance, L. culpaeus is a generalist species capable of using a wide variety of resources, switching from one to another when the abundance of a given prey decreases (Pia, ). Accordingly, weak or no local adaptive change in cranial structures is expected.…”
Section: Discussionmentioning
confidence: 99%